PEMANFAATAN METODE SEMI-ANALITIK UNTUK PENENTUAN BATIMETRI MENGGUNAKAN CITRA SATELIT RESOLUSI TINGGI - Setiawan, Kuncoro T.; Winarso, Gathot; Ginting, Devica N. BR.; Manessa, M.D.M.; Surahman, Surahman; Anggraini, Nanin; Hartuti, Maryani; Asriningrum, Wikanti; Parwati, Ety (Jurnal Penginderaan Jauh dan Pengolahan Data Citra Digital, 2021)
Semi-Analytical methods for detecting bathymetry using medium resolution satellite image data is the development of methods for determining satellite-based bathymetry. This method takes into account the principle of the propagation of light waves in water and the intensity of incident light which decreases according to the increase in depth traversed. The satellite image used is SPOT 7. The image is the latest generation of SPOT satellites which have 4 multispectral channels with a spatial resolution of 6 meters. Therefore, this high-resolution image is expected to produce bathymetry in shallow marine waters more accurately. Semi-analytical methods used to detect bathymetry are Benny and Dawson's methods. This method uses a comparison of the reflectance value between deep water and shallow water by taking into account the approach of the water column attenuation coefficient and the elevation angle of the satellite. The purpose of this study is to detect bathymetry in shallow sea waters. The study area is Karimunjawa Island coastal waters, Jepara, Central Java. The data used is the SPOT 7 acquisition image dated 18 May 2017 has been analysed, in situ depth data as well as tide data. The results showed that off the three SPOT 7 channels, the depth range of 0 - 11.45 meters for the blue channel band, 0 - 10.49 meters for the green channel and 0 - 9.72 meters for the channel red. The accuracy of the bathymetry detection results from the green channel shows quite good results to a depth of less than 5 meters. Green channel parameters of the Benny Dawson algorithm used are 0.3274 for Ld, 0.8932 for Lo, attenuation coefficient of 0.823 and Cosec E '0.6311272.